2002
DOI: 10.1139/b02-039
|View full text |Cite
|
Sign up to set email alerts
|

β-Tubulin and histoneH3gene sequences distinguishCryphonectria cubensisfrom South Africa, Asia, and South America

Abstract: Cryphonectria cubensis (Bruner) Hodges is the causal agent of an important stem canker disease of Eucalyptus. Previous phylogenetic studies based on sequence data have shown that C. cubensis is distinct from other species of Cryphonectria but that C. cubensis isolates reside in two distinct groups, consistent with geographical origin. Thus, isolates of C. cubensis from South America and South Africa grouped together but apart from those originating from Southeast Asia and Australia. These results were in contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 18 publications
5
41
0
Order By: Relevance
“…The LSU phylogenetic analyses and BLAST queries for the BT and ITS gene sequences showed that the isolates considered in this study were phylogenetically most closely related to Celoporthe spp. The type species of this genus, C. dispersa (Nakabonge et al 2006a), and Celoporthe isolates (CMW10779, CMW10780, CMW10781) collected from S. aromaticum trees in Indonesia (Myburg et al 2003, Nakabonge et al 2006a were included with the isolates collected from China for species identification. The partition homogeneity test (PHT) comparing the BT, ITS and TEF-1a datasets gave a PHT value of P 5 0.998, indicating that these three datasets do not have a significant conflict and could be combined for phylogenetic analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The LSU phylogenetic analyses and BLAST queries for the BT and ITS gene sequences showed that the isolates considered in this study were phylogenetically most closely related to Celoporthe spp. The type species of this genus, C. dispersa (Nakabonge et al 2006a), and Celoporthe isolates (CMW10779, CMW10780, CMW10781) collected from S. aromaticum trees in Indonesia (Myburg et al 2003, Nakabonge et al 2006a were included with the isolates collected from China for species identification. The partition homogeneity test (PHT) comparing the BT, ITS and TEF-1a datasets gave a PHT value of P 5 0.998, indicating that these three datasets do not have a significant conflict and could be combined for phylogenetic analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Before DNA extraction, isolates were grown in 2% MEA at 25 C for 5-7 d. For each isolate actively growing mycelium from one MEA plate per isolate was scraped from the surface of the medium with a sterile scalpel and transferred to 1.5 mL Eppendorf tubes. Genomic DNA was extracted with the method described by Myburg et al (1999), separated by electrophoresis on a 1% agarose gel, stained with ethidium bromide and viewed under ultraviolet (UV) light. Samples were treated with 3 mL RNase (1 mg/mL) and left overnight at 37 C to degrade RNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous phylogenetic studies based on the rRNA internal transcribed spacer (ITS) regions, β-tubulin and histone H3 genes have consistently separated C. cubensis into two well-supported clades (Myburg et al 1999b;Myburg et al 2002;Myburg et al 2003;Gryzenhout et al 2004;Myburg et al 2004;Gryzenhout et al 2006a;Gryzenhout et al 2006c). One of these, referred to as the South American clade, accommodates isolates from countries in South and Central America, as well as likely introductions into western African countries such as Cameroon, Congo and the Democratic Republic of the Congo (Myburg et al 2002;Myburg et al 2003;Roux et al 2003;Gryzenhout et al 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…One of these, referred to as the South American clade, accommodates isolates from countries in South and Central America, as well as likely introductions into western African countries such as Cameroon, Congo and the Democratic Republic of the Congo (Myburg et al 2002;Myburg et al 2003;Roux et al 2003;Gryzenhout et al 2006b). The second clade accommodates isolates from Southeast Asian countries such as Indonesia and Thailand, as well as likely introductions into Australia, China, Hawaii (Myburg et al 2002;Myburg et al 2003;Gryzenhout et al 2006b), and several countries in Eastern Africa Gryzenhout et al 2006b;Nakabonge et al 2006). Although isolates in these clades have distinct and nonoverlapping geographic distributions , they all include native hosts in the Melastomataceae.…”
Section: Introductionmentioning
confidence: 99%